Legal Protection for Salak Riring as a Geographical Indication - Raihan, Muhammad; Berlianty, Teng; Soplanit, Miracle (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Registration of geographical indication protection of Salak Riring in West Seram Regency will popularize the area as a producer of quality salak fruit, increase sales, and contribute to local economic growth. This protection also provides legal certainty for producers, protecting the product from counterfeiting and misuse. Salak Riring, also known as Salak Merah, has been recognized as a superior commodity of West Seram Regency, Salak Merah received an award in the form of a Certificate from the Minister of Agriculture of the Republic of Indonesia Number 454/KPTS/PD.210/9/2003, and was designated as a national superior variety due to its distinctive botanical characteristics and high economic value.Purposes of the Research:  The purpose is to examine and explain the legal protection of Salak Riring as a geographical indication.Methods of the Research: The research method used is normative juridical, which examines legal materials such as laws and regulations, legal theories, and opinions of scholars in order to solve the problems studied.Results of the Research: The results of this study show that the legal protection of Salak Riring as a geographical indication has a significant economic impact on the people of Riring Village in West Seram. The registration of Salak Riring provides legal protection and certainty to the community in production and marketing, and protects against counterfeiting or misuse. Salak Riring as one of the geographical indication products with special characteristics, makes legal protection a must to maintain the sustainability of quality production and sales.